2022
DOI: 10.1101/2022.06.28.498038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pick-up Single-Cell Proteomic Analysis for Quantifying up to 3000 Proteins in a Tumor Cell

Abstract: The shotgun proteomic analysis is currently the most promising single-cell protein sequencing technology, however its identification level of ~1000 proteins per cell is still insufficient for practical applications. Here, we develop a pick-up single-cell proteomic analysis (PiSPA) workflow to achieve a deep identification capable of quantifying up to 3000 protein groups in a tumor cell using the label-free quantitative method. The PiSPA workflow is specially established for single-cell samples mainly based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Subsequently, diaPASEF, which combines the advantages of DIA mode acquisition and the high efficiency of PASEF, was developed and applied, suitable for proteomic characterization of very limited samples [26,4346]. Wang et al demonstrated that diaPASEF can dramatically double the protein identification numbers compared with ddaPASEF in single mammal somatic cells [28]. Our data also showed 120% ∼ 135% improvement of protein identification using diaPASEF compared with ddaPASEF, and the higher correlation of diaPASEF proved the data reliability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, diaPASEF, which combines the advantages of DIA mode acquisition and the high efficiency of PASEF, was developed and applied, suitable for proteomic characterization of very limited samples [26,4346]. Wang et al demonstrated that diaPASEF can dramatically double the protein identification numbers compared with ddaPASEF in single mammal somatic cells [28]. Our data also showed 120% ∼ 135% improvement of protein identification using diaPASEF compared with ddaPASEF, and the higher correlation of diaPASEF proved the data reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 6, 2023. ; https://doi.org/10.1101/2023.01.06.523005 doi: bioRxiv preprint 2,000 proteins can be quantified reliably [26][27][28]. There are also several studies that have applied single-cell proteomic techniques to the oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PiSPA platform demonstrated the highest sensitivity with significant improvement in proteome depth over current SCP methods. 198…”
Section: Other Recent Developments: Proteochip Wino and Pispamentioning
confidence: 99%
“…The mass spectrometry (MS)-based technique coupled with the shotgun strategy provides an effective way to achieve non-targeted and deep single-cell proteome analysis. Recently, some MS-based systems such as SCoPE-MS 19 , Nested Nanowell chip 20,21 , Evosep 22 , and PiSPA 23 could achieve much deeper proteomic analysis with over 1000 protein groups identified in single cells, and even reaching up to 3000 protein groups using the PiSPA platform. These progress demonstrated a significant breakthrough in single-cell protein identification depth, although they have not reached a comparable level to transcriptome sequencing.…”
Section: Introductionmentioning
confidence: 99%